2022
DOI: 10.1002/pld3.377
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in response of durum wheat (Triticum durum Desf.) to lime‐induced iron chlorosis

Abstract: Wheat, durum wheat, is the first cereal cultivated and consumed in Tunisia. Because the dominance of calcareous soils in its agroecological systems, known by their low availability of iron (Fe) inducing Fe chlorosis and limiting crop production, its yield remains low. Therefore, the search for tolerant genotypes is always current. In this context, the physiological behavior of six Tunisian genotypes of durum wheat (salim, karim, razek, khiar, inrat100, and maali) cultivated on calcareous and fertile soils for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Furthermore, chlorophyll biosynthesis and photosynthesis decreased in the two genotypes while maintaining the superiority of CN. In fact, iron is known to be involved in chlorophyll biosynthesis and photosynthesis [11,33,34], as well as the metabolism of some plastidial proteins [26]. Therefore, the observed symptoms of Fe chlorosis and the associated reduction of chlorophyll biosynthesis and net photosynthetic assimilation in this study can be explained by the drastic decrease in iron availability for these key functions.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, chlorophyll biosynthesis and photosynthesis decreased in the two genotypes while maintaining the superiority of CN. In fact, iron is known to be involved in chlorophyll biosynthesis and photosynthesis [11,33,34], as well as the metabolism of some plastidial proteins [26]. Therefore, the observed symptoms of Fe chlorosis and the associated reduction of chlorophyll biosynthesis and net photosynthetic assimilation in this study can be explained by the drastic decrease in iron availability for these key functions.…”
Section: Discussionmentioning
confidence: 59%
“…Overall researchers have focused on this direct, but expensive, polluting, and unsustainable approach for iron chlorosis correction, leaving aside other efficient approaches [25]. One of these is the exploration of the available plant resources on the basis of their differences in response to iron deficiency in order to highlight tolerant genotypes and identify useful traits of tolerance [26]. In a previous study on four common bean genotypes subjected to iron deficiency, we identified genotypic variability in response to this nutritional constraint based on their rhizosphere acidification and Fe-chelate reductase activity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Various synthetic wheat lines were developed in the past by Japanese groups [ 93 ] by crossing the tetraploid wheat cultivar “Langdon” with Aegilops tauschii accessions mainly collected from Iran but also from other Asian countries; three lines with high Fe and Zn content in grains were identified; such traits were stable across the seasons [ 62 ]. Durum wheat genotypes tolerant to growth in calcareous soil were also selected [ 77 ].…”
Section: Research Hotspot: Fe Deficiency and Crops Biofortificationmentioning
confidence: 99%
“…Numerous studies have demonstrated that, even if very abundant in the soil, Fe exist mainly in poorly bioavailable inorganic forms that cannot be efficiently absorbed by plants (Darbani et al, 2013;Briat et al, 2015;Tsai and Schmidt, 2017;Venutti et al, 2019). It represents a serious problem for wheat yield in Tunisian soils (Salhi et al, 2022;Zhang et al, 2020). Induced Fe deficiency was demonstrated associated to calcareous, alkaline soils where Fe availability is low (Barhoumi et al, 2021;Krouma et al, 2008;Krouma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In plant, Fe plays a key role in redox reactions of numerous metabolic processes such as photosynthesis, respiration and nitrogen assimilation besides being involved in chlorophyll biosynthesis and phytohormones (Marschner, 1995). Photosynthesis, as one of the most important physiological processes on the Earth, is susceptible to iron deficiency (Salhi et al, 2022;Barhoumi et al, 2021;Ouled et al, 2022). Iron is essential for electron flow through the PSII-Cytb6f-PSI complex (Hantzis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%